The association of health anxiety with quality of life among medical students in Egypt: Myth or Menace? - Mohamed Terra; Mohamed Baklola; Lena Said Mansour; Nour Edin Darwish; Mennatallah Elsayed Badr; Amira A. Alghazali; Jinan Ali A. Almumtin; Fayrouz Mohamed Fahmy; Abdel-Hady El-Gilany (BMC Psychiatry)
Abstract Background Health anxiety (HA) is a prevalent concern among medical students, potentially impacting their academic performance and Quality of Life (QoL). This study aims to assess the prevalence of HA and its predictors among medical students in Egypt and its correlation with the Quality of Life. Methods A descriptive cross-sectional study was conducted during the 2022–2023 academic year across ten Egyptian medical schools. A total of 1,173 students participated by completing an online questionnaire, which included the Short Health Anxiety Inventory (SHAI) and the 12-Item Short Form Survey (SF-12). Data were analyzed using SPSS 25. Chi-square tests, crude odds ratios (COR) with 95% confidence intervals, and Pearson’s correlation coefficients were utilized for statistical analysis. A p-value ≤ 0.05 was considered statistically significant. Results This study found that 15.7% of participants experienced clinically significant HA. Female students (17.5%) and students dissatisfied with their academic performance (18%) exhibited a significantly higher prevalence of HA. A significant negative correlation was observed between HA and QoL (r = -0.393, p ≤ 0.05), with students experiencing HA reporting lower QoL scores. Key predictors of HA included female gender (OR = 1.41, 95% CI: 1.01–1.96) and lack of academic satisfaction (OR = 1.43, 95% CI: 1.04–1.96). Conclusion Health anxiety (HA) is a notable issue among Egyptian medical students, particularly affecting females and those dissatisfied with their academic performance and is closely linked to reduced quality of life. Effective interventions could enhance the overall educational experience, helping students improve their well-being and manage HA’s impacts on their personal and academic lives.